Strengthening Professional Experience for Increasing Performance Of Pekalongan Batik Tulis SMEs - ., Sutrisno; Violinda, Qristin (KnE Social Sciences, 2022)
This study aims to strengthen the professional experience of small and medium enterprises (SMEs) in Batik Tulis Pekalongan to improve their performance. Sharing knowledge related to professional experience between businesses at small and medium levels becomes difficult because SME actors have the view that sharing knowledge will create new competitors. 100 questionnaires were distributed through surveyors directly to the owners or leaders of SMEs Batik Tulis in Pekalongan Regency. The results discovered that if an SME group contributes their knowledge, the total professional experience will increase, meaning that the increase in professional experience is built by contributing knowledge with indicators of being happy to share knowledge and experience, being willing to provide training to share expertise and being open to sharing knowledge, experience and expertise. When groups of small and medium-sized business actors collect knowledge, their collective professional experience will increase. Keywords: knowledge sharing, knowledge donating, knowledge collecting, professional experienceand performance of SMEs